Analisis Pengemasan Produksi Konten Lokal pada Program “Ceria Anak” Sebagai Upaya Mempertahankan Eksistensi Program di Stasiun Jogja TV - Amelya, Latifatul Khoiri; Susilayati , Muslimah (Librarium: Library and Information Science Journal, 2025)
This study aims to analyze how the packaging of local content production in the "Ceria Anak" program is an effort to maintain the existence of the program on Jogja TV Station. This type of research is a case study and is descriptive qualitative. Data sources in this study include primary and secondary sources. Primary sources are the results of interviews with program producers, cameramen, and the master control section. Secondary sources are previous research, books, journals, websites, and other references. This data collection was carried out by conducting interviews, observations, and documentation. The results of the study indicate that through the packaging of local content with a structured production process, including pre-production, production, and post-production stages, it is able to maintain the existence of the program on Jogja TV station, especially through the "Ceria Anak" program. This program has succeeded in attracting the attention of children and has become important in children's television in Indonesia. The pre-production stage ensures efficiency, while the production process involves team coordination to produce quality content. Creative strategies and collaboration with art studios are used to present educational and interesting shows. After production, the post-production stage improves the quality of the broadcast before being uploaded to YouTube. This program also functions as a medium for education and cultural preservation, with content that integrates local cultural elements. Management is carried out systematically, and screenings in public locations expand the audience reach.